Multidimensional sentiment calculation method for Twitter based on emoticons. Issue 2 (1st June 2015) - Matthias Steinbauer, Dr Maria Indrawan-Santiago, Dr Gabriele Anderst-Kotsis, Dr; Yamamoto, Yuki; Kumamoto, Tadahiko; Nadamoto, Akiyo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a method of calculating the sentiment value of a tweet based on the emoticon role. Design/methodology/approach – Classification of emoticon roles as four types showing "emphasis", "assuagement", "conversion" and "addition", with roles determined based on the respective relations to sentiment of sentences and emoticons. Findings – Clustering of users of four types based on emoticon sentiment. Originality/value – Formalization, using regression analysis, of the relation of sentiment between sentences and emoticons in all roles.